Synthesis and application of epoxy-oligoesteric mixtures of ED-20 epoxy resin peroxide derivative during crosslinking - Bratychak, Mykhaylo; Chopyk, Natalia (Publishing House of Lviv Polytechnic National University, 2013)
The reaction of chemical modification of ED- 20 epoxy resin with isopropylbenzene hydroperoxide has been studied. The process duration effect on the reaction between resin and hydroperoxide has been determined. The possibility to use the synthesized product as a component in the process of epoxy-oligoesteric compositions crosslinking with application of hardeners various by their nature has been studied. Вивчено реакцію хімічної модифікації епоксидної смоли ЕД-20 гідропероксидом ізопропілбензолу. Встановлено вплив тривалості процесу на протікання реакції між смолою та гідропероксидом. Вивчена можливість використання синтезованого продукту, як компоненту в процесах структурування епокси-олігоестерних композицій із застосуванням різних за природою затверджувачів.
Синтез та застосування в процесах структурування епокси-олігоестерних сумішей пероксидної похідної епоксидної смоли ЕД-20
Keywords: epoxy; isopropylbenzene hydroperoxide; modification; crosslinking; gel fraction; hardener; епоксидна смола; гідропероксид ізопропіл-бензолу; модифікація; структурування; гель-фракція; затверджувач